Wear-resistant thin-layer high-strength fast-hardening repair mortar and preparation method thereof

CN122667903APending Publication Date: 2026-09-01ANHUI BESIDE NEW BUILDING MATERIALS TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610871210.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-16
Publication Date
2026-09-01

AI Technical Summary

Technical Problem

[0006]本发明旨在解决目前快硬砂浆早期强度不足、耐磨性差、抗冲击性差、无法薄层修补等技术难题,提供一种耐磨薄层高强快硬修补砂浆及其制备方法

Benefits of technology

1、该砂浆通过构建硫铝酸盐-硅酸盐-硬石膏三元协同水化体系,结合纳米增强技术和耐磨骨料复配技术,实现了超高早期强度、优异耐磨性、抗冲击性和可薄层修补的综合性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a wear-resistant thin-layer high-strength fast-hardening repair mortar and a preparation method thereof, and relates to the technical field of building materials. The repair mortar provided by the application contains, in terms of weight fractions, fast-hardening sulphoaluminate cement 260-320 parts, ordinary portland cement 60-100 parts, low-heat portland cement 10-30 parts, anhydrous hard gypsum 30-50 parts, composite wear-resistant aggregate 450-520 parts, mineral filler 30-60 parts, colorant 1-3 parts, nano-enhancing component 1-5 parts, redispersible latex powder 12-20 parts, shrinkage-reducing and crack-resistant agent 0.5-1.5 parts, high-efficiency water-reducing agent 1.6-2.4 parts, defoaming agent 0.8-1.6 parts, cellulose ether 0.1-0.3 parts, synthetic fiber 0.8-1.8 parts, early-strength accelerating and coagulating agent 0.3-0.8 parts and composite retarding agent 0.1-0.6 parts. The application constructs a ternary synergistic hydration system of sulphoaluminate cement-portland cement-hard gypsum, and is supplemented with the compounding technology of nano-enhancing and wear-resistant aggregate, so that the repair mortar is specialized for the rapid repair engineering of heavy-load traffic infrastructure, such as airport runway, highway, port and wharf and heavy-load industrial workshop, and has the advantages of ultrahigh early strength, excellent wear resistance, impact resistance and volume stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials technology, and in particular to a wear-resistant thin-layer high-strength fast-hardening repair mortar and its preparation method, which is suitable for rapid repair projects of heavy-duty transportation infrastructure such as airport runways, highways, ports and wharves, heavy-duty industrial plants, and bridge expansion joints. Background Technology

[0002] Airport runways, highways, ports, and other heavy-duty transportation infrastructure are the lifeblood of the national economy, and their integrity directly affects the safety and efficiency of transportation. These facilities, subjected to repeated crushing, impacts, and wear from heavy vehicles over long periods, are highly susceptible to damage such as potholes, cracks, spalling, and exposed aggregate. This damage develops rapidly, and if not repaired promptly, it will seriously affect driving safety and even lead to major traffic accidents.

[0003] For emergency repairs of such heavy-duty transportation infrastructure, rapid reopening of traffic is the core requirement. Simultaneously, because the repair layer bears heavy loads and wear over long periods, the repair material must possess ultra-high strength, excellent wear resistance, impact resistance, and volume stability. Furthermore, to minimize traffic disruption, the repair layer is typically required to be thin (3-5 mm), which places higher demands on the adhesion and crack resistance of the repair material.

[0004] Existing quick-setting repair mortars generally suffer from the following fatal flaws, failing to meet the needs of rapid repairs during heavy traffic: ① Insufficient early strength, long time to open to traffic: Existing quick-setting mortar usually requires 3-4 hours to reach the strength for traffic (≥20MPa), which cannot meet the requirements for rapid opening to traffic in emergency repairs; ② Poor wear resistance and short service life: Ordinary quartz sand aggregate has low hardness and poor wear resistance. Under repeated crushing by heavy vehicles, the repair layer will be worn away quickly, and the service life is usually no more than 1 year. ③ Poor impact resistance, prone to cracking and falling off: The repair material is brittle and has poor impact resistance, and is prone to cracking and falling off under the impact load of vehicles; ④ Thin-layer repair is not possible: The existing mortar has low bonding strength, and thin-layer repair (<10mm) is prone to sanding, hollowing, and peeling. ⑤ Poor volume stability and easy to crack in the later stage: Rapid hardening sulfoaluminate cement has a fast hydration rate and concentrated hydration heat, which easily produces temperature cracks and drying shrinkage cracks.

[0005] Although some fast-hardening repair materials have appeared on the market, they generally suffer from problems such as inflated strength, poor wear resistance, later strength reduction, and high price, making them unsuitable for large-scale application in engineering projects. Therefore, developing a heavy-duty fast-hardening repair mortar with ultra-high early strength, high wear resistance, impact resistance, thin-layer repair capability, and controllable cost is a major technical challenge that urgently needs to be solved in the field of transportation infrastructure maintenance, and it has extremely important engineering value and social significance. Summary of the Invention

[0006] This invention aims to solve the technical problems of insufficient early strength, poor wear resistance, poor impact resistance, and inability to perform thin-layer repairs in current fast-hardening mortars, and provides a wear-resistant thin-layer high-strength fast-hardening repair mortar and its preparation method.

[0007] To achieve the above-mentioned technical objectives, the technical solution provided by this invention is as follows: A heavy-duty, wear-resistant, thin-layer, high-strength, and fast-hardening repair mortar, by weight, comprises: 260-320 parts of fast-hardening sulfoaluminate cement, 60-100 parts of ordinary silicate cement, 10-30 parts of low-heat silicate cement, 30-50 parts of anhydrous gypsum, 450-520 parts of composite wear-resistant aggregate, 30-60 parts of mineral filler, 1-3 parts of colorant, 1-5 parts of nano-reinforcing components, 12-20 parts of redispersible latex powder, 0.5-1.5 parts of shrinkage-reducing and crack-resistant agent, 1.6-2.4 parts of high-efficiency water-reducing agent, 0.8-1.6 parts of defoamer, 0.1-0.3 parts of cellulose ether, 0.8-1.8 parts of synthetic fiber, 0.3-0.8 parts of early-strength accelerator, and 0.1-0.6 parts of composite retarder.

[0008] The core technology principles are as follows: ① Ternary synergistic hydration system: The system is mainly composed of rapid-hardening sulfoaluminate cement, which rapidly generates ettringite crystals and provides ultra-high early strength; ordinary silicate cement is used as an auxiliary agent to generate CSH gel, which fills the pores and improves density and later strength; anhydrous gypsum acts as a sulfate activator to promote the formation and growth of ettringite, while regulating the hydration process; a small amount of low-heat silicate cement is used to reduce the heat of hydration, reduce temperature cracks, and improve volume stability.

[0009] ② Nano-reinforcement technology: Nano-calcium carbonate and nano-silica can not only fill the pores of cement stone and improve its density, but also act as crystal nuclei to promote the generation and growth of hydration products. At the same time, they can improve the structure of the interface transition zone and significantly improve the strength, wear resistance and bonding performance of mortar.

[0010] ③ Wear-resistant aggregate compounding technology: Quartz sand and corundum are compounded as aggregates. Corundum has a Mohs hardness of up to 9, which significantly improves the surface hardness and wear resistance of the mortar. At the same time, the reasonable gradation design makes the aggregate packing more compact, which further improves the strength and durability of the mortar.

[0011] ④ Precise control technology for early strength and delayed setting: Lithium carbonate and calcium formate are used as early strength accelerators to significantly accelerate the hydration reaction and improve early strength; tartaric acid and boric acid are used as composite retarders to effectively delay the setting time and ensure sufficient construction operation time (15-30 min), achieving "fast hardening without instantaneous setting".

[0012] Furthermore, the rapid-hardening sulfoaluminate cement has a strength grade of 42.5 or higher, and the clinker contains ≥60% calcium sulfoaluminate (C4A3S) and ≤0.5% free calcium oxide; the ordinary silicate cement has a strength grade of 42.5R or higher; and the anhydrous gypsum has a CaSO4 content of ≥90% and a fineness of 200-400 mesh.

[0013] Furthermore, the composite wear-resistant aggregate is composed of quartz sand and corundum in a mass ratio of (3-5):1, with a continuous gradation of 40-120 mesh; the nano-reinforcing component is selected from one or more of nano-calcium carbonate, nano-silica, and nano-alumina, with an average particle size of 20-100 nm.

[0014] Furthermore, the early-strength accelerator is a compound of lithium carbonate and calcium formate in a mass ratio of 1:2-4; the composite retarder is a compound of tartaric acid and boric acid in a mass ratio of 1-3:1.

[0015] Furthermore, the shrinkage-reducing and crack-resistant agent is an organosilicon shrinkage-reducing agent; the synthetic fiber is a high-strength polypropylene fiber with a length of 3-6 mm and a tensile strength ≥400 MPa; the redispersible latex powder is an acrylate copolymer latex powder with a glass transition temperature ≤-15℃, which has excellent flexibility and bonding properties.

[0016] Furthermore, the mineral filler is 325-mesh heavy calcium carbonate; the colorant is iron oxide black; the high-efficiency water-reducing agent is a polycarboxylate-based high-efficiency water-reducing agent with a water reduction rate of ≥30%; and the defoamer is an organosilicon defoamer.

[0017] The present invention also provides a method for preparing the above-mentioned heavy-duty wear-resistant thin-layer high-strength fast-hardening repair mortar, comprising the following steps: (1) weighing all dry raw materials according to the weight parts; (2) adding fast-hardening sulfoaluminate cement, ordinary silicate cement, low-heat silicate cement, anhydrous gypsum, composite wear-resistant aggregate, mineral filler, colorant and nano-reinforcing components into a twin-shaft zero-gravity mixer and pre-stirring for 4-6 minutes until uniform; (3) adding redispersible latex powder, shrinkage-reducing and crack-resistant agent, high-efficiency water-reducing agent, defoamer, cellulose ether, synthetic fiber, early-strength accelerator and composite retarder to the mixer in sequence, and continuing to stir for 8-12 minutes until all components are uniformly dispersed; (4) packaging after inspection and approval to obtain the finished product.

[0018] The present invention has the following beneficial effects: 1. This mortar achieves comprehensive performance including ultra-high early strength, excellent wear resistance, impact resistance, and thin-layer repair by constructing a ternary synergistic hydration system of sulfoaluminate-silicate-anhydrite and combining nano-reinforcement technology and wear-resistant aggregate compounding technology.

[0019] 2. Ultra-high early strength, rapid traffic reopening: The mortar has a compressive strength of ≥25MPa after 2 hours, and traffic can be reopened 2 hours after repair, which greatly shortens the traffic closure time and minimizes the impact on traffic.

[0020] 3. Excellent wear resistance and impact resistance: It uses a blend of corundum and quartz sand as wear-resistant aggregate, supplemented by nano-reinforcement technology. The 28-day wear loss is ≤0.8kg / m², the impact resistance is more than 50% higher than that of ordinary mortar, and the service life can reach more than 5 years.

[0021] 4. It can achieve 3-5mm thin-layer repair: the bond strength with old concrete is ≥3.0MPa. There is no sanding, hollowing or falling off when repairing thin layers, which greatly reduces the amount of repair materials used and construction costs.

[0022] 5. Excellent volume stability: 28-day shrinkage ≤220×10⁻⁶ -6 This effectively prevents the repair layer from cracking and becoming hollow.

[0023] 6. Good workability: initial fluidity ≥140mm, workable time 15-30min, uniform slurry state, easy to spread and smooth, and high construction efficiency.

[0024] 7. Controllable cost: Raw materials are widely available and reasonably priced. Compared with similar imported products, the cost can be reduced by more than 50%, making it suitable for large-scale engineering applications. Detailed Implementation

[0025] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0026] Furthermore, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0027] Examples 1-4 Examples 1-4 provide heavy-duty wear-resistant thin-layer high-strength fast-hardening repair mortars, with formulations shown in Table 1. The repair mortars of each example are prepared according to the following steps: (1) Weigh all dry raw materials according to Table 1; (2) Add fast-hardening sulfoaluminate cement, ordinary silicate cement, low-heat silicate cement, anhydrous gypsum, composite wear-resistant aggregate, heavy calcium carbonate, iron oxide black and nano calcium carbonate to a twin-shaft zero-gravity mixer and pre-mix for 5 minutes until uniform; (3) Add acrylate latex powder, silicone shrinkage reducer, polycarboxylate superplasticizer, silicone defoamer, hydroxypropyl methylcellulose ether, polypropylene fiber, early-strength accelerator and composite retarder to the mixer in sequence, and continue mixing for 10 minutes until all components are uniformly dispersed; (4) After passing inspection, package to obtain the finished product.

[0028] Table 1. Formulations (kg) for Examples 1-4

[0029] Comparative Example 1 This comparative example provides a commercially available common fast-setting repair mortar that uses a single fast-setting sulfoaluminate cement as the binder, without adding nano-reinforcing components or corundum aggregate.

[0030] Experimental Example 1 The performance tests were conducted on the repair mortars prepared in Examples 1-4 and Comparative Example 1 according to GB / T 17671 "Test Method for Strength of Cement Mortar (ISO Method)", JC / T 2381 "Repair Mortar" and GB / T 16925 "Test Method for Abrasion Resistance of Concrete and its Products". The test environment temperature was 20℃ and the relative humidity was 60%. The test results are shown in Table 2.

[0031] Table 2 Performance Test Results

[0032] As can be seen from Table 2: (1) The 2-hour compressive strength of Examples 1-4 of the present invention is ≥25MPa, which can meet the requirements for rapid traffic opening, while the 2-hour compressive strength of Comparative Example 1 is only 15.2MPa, which cannot meet the requirements for rapid emergency repair of heavy traffic. (2) The 28-day wear loss of the embodiments of the present invention is only 0.65-0.75kg / m², which is much lower than 2.35kg / m² of Comparative Example 1, and the wear resistance is improved by more than 2 times. (3) The bonding strength of the embodiments of the present invention is ≥3.0MPa, which can achieve 3-5mm thin layer repair, while the bonding strength of Comparative Example 1 is only 1.8MPa, and sanding and falling off occur during thin layer repair. (4) The 28-day drying shrinkage rate of the embodiments of the present invention is ≤220×10⁻ 6 It is only about 50% of that of Comparative Example 1, and has excellent volume stability. (5) By adjusting the dosage of the composite retarder, the workable time for construction can be controlled between 15-30 minutes to meet the requirements of different construction conditions.

[0033] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

[0034] The above detailed embodiments are a description of the present invention. It should not be considered that the specific embodiments of the present invention are limited to these descriptions. For those skilled in the art, several simple deductions and substitutions can be made without departing from the concept of the present invention, and all of these should be considered to fall within the protection scope of the present invention.

Claims

1. A heavy-duty, wear-resistant, thin-layer, high-strength, fast-hardening repair mortar, characterized in that, By weight, it includes: 260-320 parts of rapid-hardening sulfoaluminate cement, 60-100 parts of ordinary silicate cement, 10-30 parts of low-heat silicate cement, 30-50 parts of anhydrous gypsum, 450-520 parts of composite wear-resistant aggregate, 30-60 parts of mineral filler, 1-3 parts of colorant, 1-5 parts of nano-reinforcing components, 12-20 parts of redispersible latex powder, 0.5-1.5 parts of shrinkage-reducing and crack-resistant agent, 1.6-2.4 parts of high-efficiency water-reducing agent, 0.8-1.6 parts of defoamer, 0.1-0.3 parts of cellulose ether, 0.8-1.8 parts of synthetic fiber, 0.3-0.8 parts of early-strength accelerator, and 0.1-0.6 parts of composite retarder.

2. The heavy-duty wear-resistant thin-layer high-strength rapid-hardening repair mortar according to claim 1, characterized in that, The rapid-hardening sulfoaluminate cement has a strength grade of 42.5 or higher, and the clinker contains ≥60% calcium sulfoaluminate and ≤0.5% free calcium oxide; the ordinary silicate cement has a strength grade of 42.5R or higher; the anhydrous gypsum has a CaSO4 content of ≥90% and a fineness of 200-400 mesh.

3. The heavy-duty wear-resistant thin-layer high-strength rapid-hardening repair mortar according to claim 1, characterized in that, The composite wear-resistant aggregate is composed of quartz sand and corundum in a mass ratio of 3-5:1, with a continuous gradation of 40-120 mesh; the nano-reinforcing component is selected from one or more of nano-calcium carbonate, nano-silica, and nano-alumina, with an average particle size of 20-100 nm.

4. The heavy-duty wear-resistant thin-layer high-strength rapid-hardening repair mortar according to claim 1, characterized in that, The early-strength accelerator is a compound of lithium carbonate and calcium formate in a mass ratio of 1:2-4; the composite retarder is a compound of tartaric acid and boric acid in a mass ratio of 1-3:

1.

5. The heavy-duty wear-resistant thin-layer high-strength rapid-hardening repair mortar according to claim 1, characterized in that, The shrinkage-reducing and crack-resistant agent is an organosilicon shrinkage-reducing agent; the synthetic fiber is a high-strength polypropylene fiber with a length of 3-6 mm and a tensile strength ≥400 MPa; the redispersible latex powder is an acrylate copolymer latex powder with a glass transition temperature ≤-15℃.

6. The heavy-duty wear-resistant thin-layer high-strength rapid-hardening repair mortar according to claim 1, characterized in that, The mortar meets the following performance requirements: 2h compressive strength ≥25MPa, 24h compressive strength ≥45MPa, 28d compressive strength ≥70MPa; 28-day abrasion loss ≤ 0.8 kg / m²; 28-day shrinkage rate ≤ 220 × 10⁻ 6 ; Bond strength with old concrete ≥3.0MPa; It can achieve 3-5mm thin-layer repair without sanding or peeling.

7. A method for preparing the heavy-duty wear-resistant thin-layer high-strength rapid-hardening repair mortar according to any one of claims 1-6, characterized in that, Includes the following steps: Step 1: Weigh all dry raw materials according to the specified weight proportions; Step 2: Add rapid-hardening sulfoaluminate cement, ordinary silicate cement, low-heat silicate cement, anhydrous gypsum, composite wear-resistant aggregate, mineral filler, colorant and nano-reinforcing components to a twin-shaft zero-gravity mixer and pre-mix for 4-6 minutes until homogeneous. Step 3: Add redispersible latex powder, shrinkage-reducing and crack-resistant agent, high-efficiency water-reducing agent, defoamer, cellulose ether, synthetic fiber, early-strength accelerator and composite retarder to the mixer in sequence, and continue to stir for 8-12 minutes until all components are evenly dispersed; Step 4: After passing inspection, package the product to obtain the finished product.